The role of earnings quality in the impact of earnings management and leverage on firm value - Ishak, Jouzar Farouq (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study examines the impact of earnings management and leverage on firm value with earnings quality as an intervening variable. Research methodology Quantitative methods were used in this study, which employed path analysis to examine the relationships between variables. Samples were taken from state-owned enterprises in Indonesia, with a particular focus on those listed on the 2017-2021 BUMN 20 Index of the Indonesia Stock Exchange. Results: The results show that earnings quality mediates the relationship between leverage and firm value. Specifically, leveraging through earnings quality was found to maximize firm value, as profitable businesses prioritized internal financing because of their high rate of return. Limitations: This study was limited to the IDX BUMN 20 index between 2017 and 2021. Contribution: The findings suggest that management should consider leveraging to optimize firm value. In addition, it provides valuable insights into firm value, particularly for firms that rely heavily on internal financing. Novelty: This research is the first study to specifically focus on the IDX BUMN 20 index, covering both the periods before and during the Covid-19 pandemic.